FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi pada perusahaan Food and Beverage di BEI Periode 2015-2018) - Haris Maulana; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACK This research aims to determine the influence of company size, asset structure and profitability on the capital structure in part (partial) or simultaneously (simultaneous). This research uses secondary data. This study is a variable size of the company, asset structure and profitability as an independent variable, while the dependent variable is a capital structure. The sampling technique is based on the criteria that have been determined using the purposive sampling method, then 8 Food and Beverage companies are obtained on the IDX in the period 2015-2018, and the data analysis method uses descriptive analysis and multiple linear regression analysis. By testing the data includes normality test, classic assumption test, and hypothesis testing. The results of the analysis show: Simultaneously the independent variables namely company size, asset structure, and profitability have a significant effect on the dependent variable capital structure, partially the size of the company has a significant effect on capital structure, asset structure has a significant effect on capital structure and profitability has a significant effect on capital structure Keyword: corporate size, asset structure, profitability, capital structures